Placenta Percreta in a Gravid Bicornuate Unicollis Uterus - Sammy Ngichabe; Mandeep Sura (Case Reports in Obstetrics and Gynecology)
Background. Identifying bicornuate uterus can be challenging especially as a cause of early pregnancy bleeding. On ultrasonographic examination, it is difficult to misdiagnose pregnancy in a bicornuate uterus as an ectopic pregnancy due to the continuity of the endometrium. A rudimentary horn of a bicornuate uterus in early pregnancy can occasionally be misdiagnosed for an ectopic pregnancy especially when compounded by severe abdominal pains and supportive sonographic evidence. Myometrial invasive grading of placenta may be necessary for emergency preparedness and consenting. Hemihysterectomy is lifesaving when percreta has caused severe postpartum haemorrhage. Case Presentation. We present a 24-year-old primigravida who presented to the maternity department with severe abdominal pains at 35 weeks. She was pale on clinical examination and haemodynamically unstable. She underwent emergency caesarean section with a preoperative diagnosis of concealed abruptio placentae. Intraoperatively we encountered a bicornuate uterus, delivered a fresh stillbirth, and noted a placenta percreta. A hemihysterectomy was done and she recovered after transfusion without complications. Conclusion. A gravid horn of a bicornuate uterus may present as an ectopic pregnancy; careful assessment at laparotomy or laparoscopy is required to prevent inadvertent surgical termination of pregnancy. Placental myometrial invasive assessment is important for delivery emergency preparedness.